An insight in to isolation of natural products derivedfrom macrofungi as antineoplastic agents: A Review - Fernando, Dilusha; Senathilake, Kanishka; Nanayakkara, C.M.; de Silva, E. Dilip; Wijesundera, Ravindra L; Soysa, Preethi; de Silva, Nissanka (International Journal of Collaborative Research on Internal Medicine & Public Health, 2018)
Macrofungi have been valued as medicinal provisions for humankind and are a rich source of natural anticancer compounds. However, the isolation of such compounds from macrofungi is challenging. This review highlights the importance and challenges that meet during an isolation of anticancer compounds from macrofungi. Moreover, it exhibits the impact of potential anticancer compounds and antioxidants derived from different kinds of mushrooms in decreasing the risk of cancer. It also displays the capacity to develop more effective anticancer drugs using natural antineoplastic agents of macrofungal origin.
Keywords: Macrofungi, Anticancer activity, Anticancer compounds, Antioxidants,Cancer, Antineoplastic drugs